Correlation of Gingival Thickness with Gingival Width, Probing Depth and Papillary Fill in Mandibular Anterior Teeth - Balaji, Smriti; Gajendran, Priyalochana (Research journal of pharmacy and technology, 2018)
[...]there is a need to convert thin biotype to a thick biotype. [...]the aim of the study is to correlate the gingival thickness, gingival width, papillary fill and probing depth in relation to mandibular lower anteriors. Age: 19 to 35 years Exclusion criteria: a) Subjects with crown or restorations b) Fixed or removable orthodontic treatment c) Subjects with clinical signs of periodontal disease d) Pregnant women e) Subjects taking medication with any known effect on the periodontal soft tissues Gingival thickness (GT) was evaluated based on the probe transparency method. The particular shape, topographical distribution and width of the gingiva are clearly functions of the presence and position of erupted teeth. [...]tooth shape itself seems to have an important impact on the clinical features of the surrounding gingiva and probably also the underlying tooth supporting periodontal tissues2.